Laser‐Induced Graphene Formation on Wood. Issue 37 (24th July 2017) - Ye, Ruquan; Chyan, Yieu; Zhang, Jibo; Li, Yilun; Han, Xiao; Kittrell, Carter; Tour, James M.
Abstract : Wood as a renewable naturally occurring resource has been the focus of much research and commercial interests in applications ranging from building construction to chemicals production. Here, a facile approach is reported to transform wood into hierarchical porous graphene using CO2 laser scribing. Studies reveal that the crosslinked lignocellulose structure inherent in wood with higher lignin content is more favorable for the generation of high‐quality graphene than wood with lower lignin content. Because of its high electrical conductivity (≈10 Ω per square), graphene patterned on wood surfaces can be readily fabricated into various high‐performance devices, such as hydrogen evolution and oxygen evolution electrodes for overall water splitting with high reaction rates at low overpotentials, and supercapacitors for energy storage with high capacitance. The versatility of this technique in formation of multifunctional wood hybrids can inspire both research and industrial interest in the development of wood‐derived graphene materials and their nanodevices. Abstract : Laser‐induced porous graphene (LIG) is formed on wood by laser irradiation. This LIG is engineered into energy‐storage devices and electrocatalysis electrodes. The LIG from pine (P‐LIG) is coated with polyaniline to form supercapacitors and with metals Co, Ni, and Fe to form electrocatalysts. The electrocatalysis of water using metal‐coated P‐LIG produces H2 and O2 .